2016
DOI: 10.1080/03081087.2016.1216517
|View full text |Cite
|
Sign up to set email alerts
|

Optimal estimates for summing multilinear operators

Abstract: We show that given a positive integer m, a real number p ∈ [2, ∞) and 1 ≤ s < p * the set of non-multiple (r; s)-summing m-linear forms on p × · · · × p contains, except for the null vector, a closed subspace of maximal dimension whenever r < 2ms s+2m−ms . This result is optimal since for r ≥ 2ms s+2m−ms all m-linear forms on p × · · · × p are multiple (r; s)-summing. In particular, among other results, we generalize a result related to cotype (from 2010) due to Botelho et al.The classical Bohnenblust-Hille in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…(ℓ p * 0 , ℓ p * 1 ); (X 0 , X 1 ) and (3) (ℓ p * 0 , ℓ p * 1 ); (ℓ 1 , ℓ 1 ) satisfy the injective θ-property for any 0 < θ < 1. For the family (1) we have…”
Section: Interpolation Of Tensor Products and Coincidence Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ℓ p * 0 , ℓ p * 1 ); (X 0 , X 1 ) and (3) (ℓ p * 0 , ℓ p * 1 ); (ℓ 1 , ℓ 1 ) satisfy the injective θ-property for any 0 < θ < 1. For the family (1) we have…”
Section: Interpolation Of Tensor Products and Coincidence Resultsmentioning
confidence: 99%
“…, X m and all r ≥ 1. In [3], it was observed that this is optimal in the following sense: L( m c 0 , . .…”
Section: It Satisfiesmentioning
confidence: 99%
“…Theorem 1 is in some sense optimal. In fact it was recently proved in [4] that the Defant-Voigt Theorem is optimal in the following sense: every continuous m-linear form is absolutely (1; 1, ..., 1)summing and this result can not be improved to (p; 1, ..., 1)-summing with p < 1.…”
Section: Remark 1 the Constant C That Appears In The Above Theorem Cmentioning
confidence: 99%
“…We shall need the following coincidence theorem that can be essentially found in [2,4] to obtain estimates of the indices of summabilitity along this paper.…”
Section: Some Upper Estimates For the Index Of Summabilitymentioning
confidence: 99%